Rails to Ruin: The E&N and Settler Views of Vancouver Island - Holland, Samuel (the ascendant historian, 2024)
The construction and operation of the Esquimalt and Nanaimo railway (E&N) on Vancouver Island is a relatively understudied area of British Columbia history. This is despite the place of the E&N in effectively creating the current systems of industrial exploitation and recreational use on Vancouver Island. The E&N and its land grant shaped the legal, political, military, ecological, and geographic history of the region. Legally and politically, the construction of the E&N was the impetus for mass land seizure by the Provincial government. Militarily, the railroad was important in securing the British Empire’s operations in the Pacific, supplying an important coaling station. Ecologically, the E&N opened much of the island to exploitation in the form of mining and logging, as well as settlement. Geographically, the E&N connected the island to Victoria by land, transforming the relationship of people to the island both temporally (it was faster to travel than on steamship) and conceptually (new stops along the line participated in placemaking for settlers and visitors). I examine the place of the E&N in these historical areas and contextualize the seizure of aboriginal title on Vancouver Island in terms of three competing views of landscape: pastoral, industrial, and recreational. These three views provide an excellent lens for understanding the transformation of Vancouver Island throughout the 20th century, including the displacement of Indigenous peoples, the development of industry, recreational uses, and even early conservationist views.